Evaluation of reservoir environment by chemical properties of reservoir water‒A case study of Chang 6 reservoir in Ansai oilfield, Ordos Basin, China - Zhi-bo Zhang; Ying Xu; Di-fei Zhao; Hao-ming Liu; Wei-cheng Jiang; Dan-ling Chen; Teng-rui Jin (China Geology)
ABSTRACT: The Ordos Basin is the largest continental multi-energy mineral basin in China, which is rich in coal, oil and gas, and uranium resources. The exploitation of mineral resources is closely related to reservoir water. The chemical properties of reservoir water are very important for reservoir evaluation and are significant indicators of the sealing of reservoir oil and gas resources. Therefore, the caprock of the Chang 6 reservoir in the Yanchang Formation was evaluated. The authors tested and analyzed the chemical characteristics of water samples selected from 30 wells in the Chang 6 reservoir of Ansai Oilfield in the Ordos Basin. The results show that the Chang 6 reservoir water in Ansai Oilfield is dominated by calcium-chloride water type with a sodium chloride coefficient of generally less than 0.5. The chloride magnesium coefficients are between 33.7 and 925.5, most of which are greater than 200. The desulfurization coefficients range from 0.21 to 13.4, with an average of 2.227. The carbonate balance coefficients are mainly concentrated below 0.01, with an average of 0.008. The calcium and magnesium coefficients are between 0.08 and 0.003, with an average of 0.01. Combined with the characteristics of the four-corner layout of the reservoir water, the above results show that the graphics are basically consistent. The study indicates that the Chang 6 reservoir in Ansai Oilfield in the Ordos Basin is a favorable block for oil and gas storage with good sealing properties, great preservation conditions of oil and gas, and high pore connectivity.©2023 China Geology Editorial Office.